Central European History and the European Union The Meaning of Europe - Kirschbaum, S.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
This is a volume of scholarly essays that considers the meaning of Europe by examining aspects of Central European history as well as issues dealing with the EU's enlargement into Central Europe. These factors contribute to ideas of a definition of Europe that reflects the values and aspirations of all its citizens.
Keywords: European Union; Europe—Politics and government; Political science; Europe—History.; International relations; European Union Politics; European Politics; Political Science; European History; International Relations